2014
DOI: 10.1682/jrrd.2013.02.0049
|View full text |Cite
|
Sign up to set email alerts
|

Visual function, traumatic brain injury, and posttraumatic stress disorder

Abstract: Abstract-Traumatic brain injury (TBI) and posttraumatic stress disorder (PTSD) are signature injuries of the Iraq and Afghanistan conflicts. The conditions can be comorbid and have overlapping signs and symptoms, making it difficult to diagnose and treat each. TBI is associated with numerous changes in vision function, but vision problems secondary to PTSD have not been documented. To address this shortcoming, we reviewed the medical records of 100 patients with a history of TBI, noting PTSD diagnoses, visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…In support of this is recent work by Goodrich et al that shows the prevalence of light sensitivity is significantly higher in Veterans with comorbid TBI and PTSD (31/38 subjects; 82%), compared to those with only TBI (13/48 subjects; 27%). 46 Additionally, previous work in a sample of 1,114 of civilians with TBI demonstrated that subjective light and noise sensitivity were significant independent predictors of PTSD symptomology. 47 The authors speculated that the presence of light and noise sensitivity perpetuated subject's awareness of their traumatic event/injury, 48 while impeding fear extinction through second-order conditioning.…”
Section: Sensory Sensitivity and Ptsdmentioning
confidence: 94%
“…In support of this is recent work by Goodrich et al that shows the prevalence of light sensitivity is significantly higher in Veterans with comorbid TBI and PTSD (31/38 subjects; 82%), compared to those with only TBI (13/48 subjects; 27%). 46 Additionally, previous work in a sample of 1,114 of civilians with TBI demonstrated that subjective light and noise sensitivity were significant independent predictors of PTSD symptomology. 47 The authors speculated that the presence of light and noise sensitivity perpetuated subject's awareness of their traumatic event/injury, 48 while impeding fear extinction through second-order conditioning.…”
Section: Sensory Sensitivity and Ptsdmentioning
confidence: 94%
“…The characteristics of the visual symptoms differed between those with or without anxiety/depression, particularly regarding reading difficulties, blurred vision, light sensitivity, light-dependent issues, and an increased tendency to bump into objects or persons. Goodrich et al (21) found that the TBI-PTSD group experienced more problems, especially regarding light sensitivity and reading difficulties. These symptoms are among those with the highest diversity in our study, and one may speculate that there might be an association between certain visual symptoms and anxiety/depression.…”
Section: Visual Deficits and Anxiety/depressionmentioning
confidence: 99%
“…The visual system is highly integrated in the processes of cognition and emotion and it is possible that interference with the visual system may lead to increased levels of depression and anxiety (19,20). Goodrich et al described differences in visual symptoms in patients with traumatic brain injury (TBI) or both TBI and post-traumatic stress disorder (PTSD).The groups were rather similar regarding visual symptoms, although the TBI-PTSD patients reported more light sensitivity and more reading problems (21). Another treatment relating the vision and emotion is Eye Movement Desensitization and Reprocessing (EMDR), which is a method used for PTSD, in which horizontal eye movements are used as a tool for the treatment (22).…”
mentioning
confidence: 99%
“…Our understanding of visual dysfunction in humans is based, in part, on post‐mortem analyses and retrospective studies involving questionnaires and review of medical records (Capo‐Aponte et al, ; Goodrich et al, ; Hellerstein, Freed, & Maples, ; Magone, Kwon, & Shin, ) (Table ). While useful in identifying the diversity of blast‐related injuries (Lew et al, ), retrospective studies can differ widely in the methodologies used to assess and classify pathologies.…”
Section: Visual System Dysfunction From Blast Injury In Humansmentioning
confidence: 99%
“…Commonly reported impairments include problems with accommodation, saccades and pursuits, vergence, integrity of the visual field, and photophobia (Alvarez et al, 2012;Bulson, Jun, & Hayes, 2012;Our understanding of visual dysfunction in humans is based, in part, on post-mortem analyses and retrospective studies involving questionnaires and review of medical records (Capo-Aponte et al, 2012;Goodrich et al, 2014;Hellerstein, Freed, & Maples, 1995;Magone, Kwon, & Shin, 2014) (Table 1). While useful in identifying the diversity of blast-related injuries (Lew et al, 2009(Lew et al, , 2011, retrospective studies can differ widely in the methodologies used to assess and classify pathologies.…”
Section: I S U a L S Y S T E M D Y S F U N C T I O N Fr O M B L Amentioning
confidence: 99%